Nanosystem functionalization strategies for prostate cancer treatment: a review. (14th September 2021) - de Araújo, Jennifer Thayanne Cavalcante; Duarte, Jonatas Lobato; Di Filippo, Leonardo Delello; Araújo, Victor Hugo Sousa; Carvalho, Gabriela Corrêa; Chorilli, Marlus
Abstract: Prostate cancer (PC) has a high morbidity and mortality rate worldwide, and the current clinical guidelines can vary depending on the stage of the disease. Drug delivery nanosystems (DDNs) can improve biopharmaceutical properties of encapsulated anti-cancer drugs by modulating their release kinetics, improving physicochemical stability and reducing toxicity. DDN can also enhance the ability of specific targeting through surface modification by coupling ligands (antibodies, nucleic acids, peptides, aptamer, proteins), thus favouring the cell internalisation process by endocytosis. The purposes of this review are to describe the limitations in the treatment of PC, explore different functionalization such as polymeric, lipid and inorganic nanosystems aimed at the treatment of PC, and demonstrate the improvement of this modification for an active target, as alternative and promising candidates for new therapies.